Saccharomyces cerevisiae Yeast-Based Supplement and Breast Milk Supply: A Randomised Placebo-Controlled Trial - Jia L; Brough L; Weber JL (John Wiley and Sons Ltd, 2025)
Saccharomyces cerevisiae yeast-based supplements (SCYS) are frequently used as galactagogues with limited evidence of their efficacy. This study investigates the effect of SCYS on human milk oligosaccharide (HMO) concentration and indicators of milk supply. Sixty-eight breastfeeding women with a healthy singleton infant aged 1–7 months were randomly assigned to consume a SCYS product (5 g/day) or placebo for 4 weeks. The primary outcome was the change in the total HMO concentration. The secondary outcomes included participants' perceptions of milk supply, intervention effectiveness, postnatal distress, infant feeding patterns, infant anthropometry, and adverse effects. Intention-to-treat analysis was performed. Multivariable linear regression analysis showed no significant effect of SCYS on individual or total HMO concentrations. However, 65% of women in the SCYS group, compared to 35% in the placebo group, perceived an increase in milk production (p < 0.05). No significant differences were found for other secondary outcomes. However, mothers in the SCYS group had a small but significant improvement in perception of their milk quantity and quality (p < 0.05). SCYS use was also associated with significantly lower formula use at 6 months postpartum (4% vs. 27%, p < 0.05). While SCYS does not impact HMO concentration, it may improve women's perceptions of milk supply. A larger randomised controlled trial is needed to assess its potential effects on actual milk production and composition and address issues of perceived insufficient milk. Trial Registration: This trial was registered at the Australian New Zealand Clinical Trials Registry (trial registration number: ACTRN12619000704190).
Keywords: breastfeeding; galactagogue; human milk oligosaccharide; human milk production; perceived insufficient milk; randomised placebo‐controlledtrial; Saccharomyces cerevisiae yeast